Plant non-coding RNAs function in pollen development and male sterility - Nie, Hushuai; Cheng, Cheng; Kong, Jie; Li, Huijing; Hua, Jinping (Frontiers in Plant Science, 2023)
Male sterility is classified as cytoplasmic male sterility (CMS) and genic male sterility (GMS). Generally, CMS is involved mitochondrial genomes interacting with the nuclear genome, and GMS is caused by nuclear genes alone. Male sterility can be regulated by multi-level mechanisms in which non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and phased small interfering RNAs (phasiRNAs), have been proved to play critical elements in male sterility occurred. The development of high-throughput sequencing technology offers new opportunities to evaluate the genetic mechanism of ncRNAs in plant male sterility. In this review, we summarize critical ncRNAs that regulate gene expression in ways dependent or independent on hormones, which involve the differentiation of stamen primordia, degradation of the tapetum, microspore formation, and pollen release. In addition, the key mechanisms of miRNAs-lncRNAs-mRNAs interaction networks mediating male sterility in plants were elaborated. We present a different perspective on exploring ncRNA-mediated regulatory pathways that control CMS in plants, and creating male sterile lines through hormones or genome editing. A refined understanding of ncRNAs regulatory mechanisms in plant male sterility to develop new sterile lines would be conducive to improve hybridization breeding industries.